Study on the mechanism and process of a universal preparation of carbon nanotubes uniform dispersions in aqueous solution. (3rd July 2020) - Zhang, Jianwei; Yang, Cheng; Wei, Fengqi; Mei, Huanhuan; Wang, Xuewen
Abstract: One of the most important factors restricting the application of carbon nanotubes (CNTs) is how to uniformly disperse CNTs in liquid phase. In this paper, the mechanism of non-covalent modification of carbon nanotubes has been studied by using the method of all-atom molecular dynamics simulation, and the corresponding experiments have been carried out to verify the obtained mechanism. The results show that non-covalent modification is an effective way to disperse carbon nanotubes. The morphology of surfactants on the surface of carbon nanotubes is an important factor for stable dispersion. This research will provide a more detailed explanation for the interaction of all atoms in dispersing process and guide the dispersing experiment in order to promote the industrial application of CNTs.